Digital Modules in Research Team-Based Learning in Higher Education: A Theoretical Review - Filma Alia Sari; Ahmad Fauzan; Oriza Candra; Muhammad Yogi Riyantama Isjoni; Aulia Apriani; Yola Yolanda (STAI Hubbulwathan Duri, 2025)
The integration of digital modules in higher education has become increasingly vital in enhancing student engagement, collaboration, and critical thinking, especially in post-pandemic learning environments. Research Team-Based Learning (RTBL) is a collaborative pedagogy that emphasizes problem-solving, peer interaction, and research-based inquiry. This theoretical review explores the role of digital modules in supporting RTBL by synthesizing findings from 15 international open-access studies published between 2020 and 2025. Using a narrative review method guided by PRISMA procedures, studies were selected from reputable databases (e.g., DOAJ, PLOS ONE, Frontiers) based on criteria including relevance to RTBL and use of digital instructional materials. Thematic analysis identified four dominant themes: student engagement, digital literacy, instructional design, and post-pandemic implications. Findings indicate that digital modules enhance the effectiveness of RTBL by providing flexible access to learning materials, promoting active participation, and enabling peer-to-peer interaction. However, their impact is highly dependent on students’ digital literacy, the quality of instructional design, and institutional infrastructure. Poorly designed modules or limited digital skills can hinder collaborative learning outcomes. This review concludes that digital modules are not merely supplementary tools but essential enablers of RTBL success. Their implementation requires a balanced strategy that integrates pedagogical, technological, and institutional support. Future research should explore longitudinal impacts, AI-driven instructional feedback, and cross-cultural adaptations to optimize the use of digital modules in collaborative higher education settings.